Indonesia’s National Sea Policy: Concretising the Global Maritime Fulcrum - Keoni Marzuki (2017)
A presidential regulation on Indonesia’s National Sea Policy recently issued by President Joko Widodo (Jokowi) incorporates the Global Maritime Fulcrum and outlines a number of strategies to fulfil Indonesia’s maritime aspiration.